Why do we feel bored with our clothing and where does it end up?. (11th October 2019) - Kwon, Theresa Anna; Choo, Ho Jung; Kim, Youn‐Kyung
Abstract: Boredom reflects the dynamic nature of consumer tastes and preferences. Understanding the role of boredom in clothing disposal is of particular importance given that consumers often dispose of clothes they feel bored with, leading to harmful environmental consequences. Despite its substantial influence on postacquisition behaviours, boredom has received insufficient attention in the disposal literature. In this paper, we explore the factors that lead to boredom and the effect of boredom on retention, recycling and discarding of clothing. We use a sequential mixed‐methods approach, consisting of a first qualitative phase that uses in‐depth interviews to generate hypotheses, followed by a second quantitative phase that tests the hypotheses using survey data. In two phases, we identify the oldness of clothing, decreased social fit and purchase of new clothing as drivers of boredom, which implies that the physical and aesthetic attributes of the clothing, social meaning ascribed to the clothing and situational factors collectively influence feelings of boredom towards owned clothing. As boredom intensifies, consumers are less inclined to keep the item and more inclined to recycle or discard it. Furthermore, we find that attachment and resource input (i.e., money, time and effort) moderate the effect of boredom on decisions regarding disposal methods. The results add to our understanding of emotion‐laden disposal by revealing the role of boredom in clothing disposal. Finally, our findings call for the collective efforts of consumers, retailers, campaigners and policymakers to break away from an increasingly extravagant and wasteful culture of clothing consumption.